Gene Dosage at the Autoflowering Locus Effects Flowering Timing and Plant Height in Triploid Cannabis - Lauren E. Kurtz; Mark H. Brand; Jessica D. Lubell-Brand (Journal of the American Society for Horticultural Science, 2023)
There is demand for early-flowering cannabis (Cannabis sativa) cultivars to hasten harvest and avoid late-season detrimental weather conditions. A field study and greenhouse studies were conducted to evaluate the effect of gene dosage at the autoflowering locus on flowering timing for diploid and triploid hybrids between autoflowering and photoperiod-sensitive parents. Autoflowering × photoperiod-sensitive hybrids were all photoperiod sensitive, but their critical photoperiods were longer than for homozygous photoperiod-sensitive plants, which resulted in earlier flowering. For triploid genotypes, decreasing dosage of the photoperiod-sensitive allele (A), from AAA to AAa to Aaa, reduced the time to flowering. Flowering timing for the diploid genotype Aa was intermediate between Aaa and AAa. These results provide evidence of incomplete dominance of the A allele at the autoflowering locus. Plants of genotype Aaa flowered 32 to 40 days earlier in the field than genotypes of AA, 15 days earlier than genotype Aa, and were ready for harvest by the second week of August in Connecticut. Plants of Aaa were as tall as other diploid and triploid photoperiod-sensitive genotypes studied, which suggests that they have similar yield potential. The use of tetraploid autoflowering (aaaa) maternal plants in combination with diploid photoperiod-sensitive (AA) pollen parents to produce Aaa genotype seed is a reliable approach for developing early-flowering cultivars of cannabis for flower production purposes.